ASPEK TEKNIS PENERAPAN CARA PEMBENIHAN IKAN YANG BAIK (CPIB) PADA IKAN KERAPU TIKUS (Cromileptes altivelis) - Akhmad Romadlon; Sholihin Sholihin (Faculty of Science and Technology University Ibrahimy, 2013)
Implementation way fish grouper (Cromileptes altivelis) were both preceded drying bath for 3 days, disinfectant such as chlorine with a dose of 150 ppm for 2 days, after which the tub is washed with detergent and rinsed freshwater. Before the use of sea water and filtered with filterbag ditreatmen use becarbon 10 tablets / m3. Disease-free eggs mouse grouper (Specific Pathogen Free) is confirmed by PCR analysis in the laboratory and Environmental Diseases BBAP Situbondo. Do daily recording include age larvae, the larvae conditions, the use of algae, rotifers density, artemia density, the use of artificial feed, change the water, siphon, water quality include temperature, DO, pH and Nitrite. Before entering the area of ​​detergent and disinfectant hand washed using 70% alcohol, so also when out of a hatchery. After the morning activities floorspace sprayed fresh water, and once a week dikaporit work floor. The production equipment (slang siphon, siphon stick, dipper, bucket, grading and other equipment) soaked in 10 ppm chlorine solution for 15 minutes then washed with detergent and rinsed freshwater. The results of field observations indicate an increase Survival Rate of 7.5-10% to 17-20% with the quality of the fish that defects decreased from 5 -7% to 1.5 - 2%. Faster growth of fish where the total length parameter on the D-60 increased from 2.5 - 3 cm to 2.8 to 3.7 cm.